Development and psychometric testing of the care dependence perception questionnaire. (17th March 2021) - Piredda, Michela; Candela, Maria Luigia; Marchetti, Anna; Biagioli, Valentina; Facchinetti, Gabriella; Gambale, Giulia; Labbadia, Chiara; Petitti, Tommasangelo; Migliore, Simone; Iacorossi, Laura; Mecugni, Daniela; Rasero, Laura; et al.
Abstract: Objective: This multicentre study aimed to develop a measure of the perception of care dependence in patients diagnosed with cancer and to test its psychometric properties. Methods: The questionnaire was developed based on findings emerged from a meta‐synthesis and from qualitative studies conducted in three hospitals in Italy. The draft questionnaire was tested for face and content validity and pilot‐tested with patients. The questionnaire was completed by care‐dependent patients with cancer. Test‐retest was conducted to verify stability. Exploratory factor analysis (EFA) was performed using a Maximum Likelihood robust estimator. Results and conclusion: The Scale‐Content Validity Index was 0.92. The final 15‐item questionnaire was completed by 208 patients admitted to two hospitals. The EFA yielded a two‐factor model including a positive and a negative perception of care dependence. Factor score determinacy coefficients, Cronbach's alpha coefficients, composite reliability coefficients and Intraclass Correlations Coefficients yielded satisfactory results confirming internal consistency and stability. The hedonic balance score is also available as a single indicator of subjective well‐being. The study provides initial validation of the Care DEeP Questionnaire that can be used by cancer nurses to assess positive and negative patient experiences with care dependence and to personalise and improve their care.